FASIES DAN PERUBAHAN LINGKUNGAN PENGENDAPAN KUARTER DI DAERAH LABUHAN (BELAWAN), SUMATERA UTARA - Herman Mulyana; Herman Moechtar (Pusat Survei Geologi, 2008)
The Quaternary deposits in the Labuhan, Belawan, North Sumatera, have been studied. These deposits have been correlated, using sections on 1:100 scale. Â From the correlation of thirteen boring logs, the Quaternary sediments can be divided into facies: (a) marine, (b) beach, (c) marsh, (d) floodbasin, and (e) fluvial channels. Furthermore, the Quaternary sediment consists of 4 (four) depositional cycles namely interval A, B, C, and D.The stratigraphic succession of Quaternary and basin fill in the studied area were influenced by global events. Changes in climatological conditions between sub-humid to optimum into subhumid to dry are the effect from Milankovitch cycles; and sea-level fluctuations from high sea-level into maximum to low sea-level were correlated to global changes of sea-level.Â Keywords: sedimentary environment, climate, sea-level, global